Emotional intelligence and demographic differences among students in public universities - Ahmad Marzuki, Najib; Mustaffa, Che Su; Mat Saad, Zarina; Muda, Suhaini; Abdullah, Suhanim; Che Din, Wan Bee (Emerging Academy Resources, 2012)
Emotional intelligence is the grassroots of all intelligence dimensions. It provides individuals with the ability to understand one’s own emotions, managing it and hopefully be able to understand other people emotions as well.The purpose of this research is to determine the emotional intelligence level of Malaysian university students from demographic aspects (gender, academic background, place of residence, academic courses and cumulative grade point average (CGPA). The importance of studying emotional intelligence in students is imperative since it indicates other competencies such as communication and interpersonal relations. A total of 3101 final year students from 10 public universities were randomly chosen as samples. The Bar-On Emotional Quotient Inventory: Short (EQ-i:S) by Bar-On (1997) has been utilized for the purpose of measuring emotional intelligence. Scores were categorized into high and low emotional intelligence level. Results were analyzed based on demographic factors such as gender, academic background, place of residence, academic courses and cumulative grade point average (CGPA).It was found that in general, majority of students were quite low in terms of emotional intelligence.Other demographic factors showed varying results.This study implicates that more should be done in higher learning institutions to alleviate and enhance students’ emotional intelligence.